The Influence Of Perception Of Benefits, Easy Of Use, Use, Trust, And Availability Of Features On Satisfaction Of Use Of Bca Mobile Banking Services (Sejabodetabek) - Lukmanul Hakim; Euphrasia Susy Suhendra (Publisher Cv. Inara, 2021)
The purpose of this study was to determine the effect of perceived usefulness, user convenience, usability, trustworthiness and feature availability on user satisfaction. The research sample consisted of 200 consumer respondents using the BCA mbanking service. Collecting data using an online questionnaire and analyzed using the AMOS program. The results show that perceived usefulness has no effect on user satisfaction, ease of use has an effect on user satisfaction, perceived usefulness has an effect on user satisfaction, trust has no effect on user satisfaction, and perceived availability of firue has an effect on user satisfactionpreferences from each macroinvertebrate species towards environmental conditions.